Production and purification of peroxidases from callus cultures of white and red cabbage for enzymatic decolourization of reactive blue 19 and acid blue 25 dyes - Öztekin, Aykut; Almaz, Züleyha); Önlü, Şeyma (TAYLOR & FRANCIS, 2021)
The removal of textile dyes from wastewater by using plant peroxidases (PODs) offers environmentally effective solutions. Therefore, researching the availability and applicability of PODs from different sources becomes important area for the sustainable process design. In this article, PODs were produced in vitro from white and red cabbage callus cultures for evaluating their potential usage to decolourization of the Reactive Blue 19 (RB-19) and Acid Blue 25 (AB-25) textile dyes for the first time. The PODs with high activity were purified 133-fold with a specific activity of 45,083 U mg(-1) and 134-fold with a specific activity of 26,785 U mg(-1) from produced white and red cabbage calluses by single-step affinity chromatography. The molecular weights of purified red cabbage callus peroxidase (r-POD) and white cabbage callus peroxidase (w-POD) were found to be as 43 and 44 kDa, respectively. In the assays to determine the r-POD and w-POD dye decolourization potential, noteworthy degradation levels were recorded for RB-19 (>85) and AB-25 (>88) dyes in the reactions catalysed by w-POD. Also, r-POD exhibited maximum decolourization efficiency of % 68 for RB-19 and %73 for AB-25 dyes under the conditions at 50 degrees C, pH 5.5 and in the presence of 4 mM H2O2.
Keywords: Callus culture; red cabbage; white cabbage; peroxidase; dye degradation